Analisis Efek Multiplier Sektor Basis Terhadap Perekonomian Kabupaten Biak Numfor 2019-2023 - Imanuel Kefas Oktovianus Fairyo; Pisi Bethania Titalessy; Yundy Hafizrianda (Universitas Cenderawasih, 2024)
This study aims to identify base sectors and analyze the magnitude of the multiplier effect of these sectors on the economy of Biak Numfor Regency during the 2019–2023 period. The study employs a quantitative approach using secondary data in the form of Gross Regional Domestic Product (GRDP) of Biak Numfor Regency and Papua Province. The analysis applies the Location Quotient (LQ) method to determine base and non-base sectors, as well as multiplier effect analysis to measure the impact of base sectors on the regional economy. The results indicate that there are nine base sectors, namely agriculture, forestry and fisheries; mining and quarrying; manufacturing; electricity and gas supply; water supply and waste management; trade; transportation; financial services; and government administration. Meanwhile, eight sectors are classified as non-base sectors, including construction; accommodation and food services; information and communication; real estate; business services; education; health services; and other services. The average multiplier effect value of 1.3059 implies that every one-unit increase in base sector output contributes to an increase in total regional economic output. However, the declining trend of the multiplier effect during the 2020–2023 period indicates weak linkages between base and non-base sectors. Therefore, local governments need to promote the development of fishery-based processing industries and enhance the capacity of non-base sectors, particularly construction, education, and health services, in order to optimize the multiplier effect and support regional economic growth. Keywords: Multiplier effect, base sector, non-base sector, Location Quotient, GRDP, Biak Numfor Regency, regional economic growth